Chapter Introduction A Global Humanities Approach to the United Nations' Sustainable Development Goals (SDGs) and Education for Sustainable Development (ESD) - Comfort, Kelly (Taylor & Francis, 2024)
The introductory chapter-"A Global Humanities Approach to the United Nations' Sustainable Development Goals (SDGs) and Education for Sustainable Development (ESD)"-first establishes the theoretical foundations of A Global Humanities Approach to the United Nations' Sustainable Development Goals: Understanding Planet, People, and Prosperity by outlining the origin, evolution, and current state of three fields: the United Nations' Sustainable Development Goals (SDGs), Education for Sustainable Development (ESD), and the Global Humanities. The Introduction then goes on to explain the methodological approach and organizational structure employed throughout the textbook. Next, it summarizes the twelve global humanities texts featured in Chapters 1-12 and includes details on the intersection of each text with the SDG framework. Finally, the opening chapter concludes with detailed guidelines for instructors on how to best use this textbook.